Oral Angiotensin-(1-7) formulation after established elastase-induced emphysema suppresses inflammation and restores lung architecture - Magalhaes, Giselle Santos; Villacampa, Alicia; Rodrigues-Machado, Maria Gloria; Campagnole-Santos, Maria Jose; Souza Santos, Robson Augusto; Sánchez-Ferrer, Carlos F.; Peiró, Concepción (Frontiers in Pharmacology, 2025)
BackgroundChronic obstructive pulmonary disease (COPD), a prevalent age-related condition, ranks among the leading causes of global mortality. It is characterized by chronic inflammation, cellular senescence, and irreversible lung tissue damage, with no curative treatments currently available. Angiotensin-(1-7) [Ang-(1-7)] has demonstrated anti-inflammatory and regenerative potential in preclinical models. This study aimed to investigate the therapeutic effects of oral Ang-(1-7) on senescence, inflammation, and tissue regeneration in a model of elastase-induced pulmonary emphysema.MethodsMale C57BL/6 mice were subjected to emphysema induction through three intratracheal instillations of porcine pancreatic elastase (PPE). One week after the final elastase instillation, the mice were treated with Ang-(1-7) encapsulated in hydroxypropyl-β-cyclodextrin to enhance its bioavailability. The treatment was administered daily for 4 weeks. Histological assessments, gene expression analysis, and protein quantification through Western blot were performed to evaluate lung architecture, inflammation, and senescence markers.ResultsThe results showed that elastase exposure led to significant lung damage, including enlarged airspaces, increased collagen deposition and upregulated expression of collagen I/III and MMP9. Markers of inflammation and senescence were significantly elevated in the untreated emphysema group. However, treatment with Ang-(1-7) reversed these changes, reducing collagen deposition, restoring alveolar structure, and suppressing inflammation and senescence. Additionally, Ang-(1-7) modulated key signaling pathways, reactivating the Wnt/β-catenin pathway for tissue regeneration and inhibiting NF-κB activation, critical for inflammation suppression.ConclusionThese findings suggest that Ang-(1-7), when administered after disease establishment, demonstrates potential to reverse structural lung damage and suppress chronic inflammation in experimental models, indicating a promising direction for future translational and clinical research in COPD.